Študijsko gradivo pri predmetu Korporacijsko in koncernsko pravo: Zbirka vaj - Prostor, Jerneja; Zdolšek, Daniel (2022)
Study Material for Corporate law and Law of Groups of Companies: A Collection of Exercises.The study material is prepared for the implementation of exercises in the pedagogical process in the subject Corporate Law and Law of Groups of Companies at the second level of Bologna law studies at the Faculty of Law, University of Maribor. The work extends to the fields of legal and economic-business sciences. The content requires a good knowledge of complex legal issues that are inseparably linked to accounting transactions. Study material is a necessary tool for those who want to build a career as commercial lawyers, and will benefit everyone to prepare for the exam in the subject of Corporate Law and Law of Groups of Companies.
Keywords: business finance; economic category monitoring; accounting; company law; corporate law